Regional favoritism and human capital accumulation in Africa - Zareh Asatryan; Thushyanthan Baskaran; Patrick Hufschmidt; Alexander Stöcker (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We study the long-run implications of regional and ethnic favoritism in Africa. Combining geocoded individual-level survey data from the Demographic and Health Survey (DHS) with data on national leaders' birthplaces across 41 African countries, we explore the educational attainment of adults who were exposed to favoritism at various points during their life. We find that generic male respondents exposed to regional favoritism during their adolescence have higher educational attainment later in life. This higher human capital accumulated by men leads to more stable employment. For generic women, we observe no beneficial effects of regional favoritism. However, those women who belong to the same ethnic group as their national leader witness an increase in their educational attainment. These results indicate that regular inhabitants rather than only a narrow elite benefit from regional favoritism.
Keywords: D73; J24; R11; 330; Favoritism; human capital; gender discrimination; democracy; spatiality; Africa